Reintegrating economy, society, and environment for cooperative futures: Polanyi, Marx, and food sovereignty - Tilzey, Mark (Journal of Rural Studies, 2016)
This paper attempts to ‘put in their place’ (Sum and Jessop 2013) some key issues that frame the question of ‘the more-than-economic dimensions of co-operation’. In particular, it asks why capitalism deconstructs socio-natural reality into the ‘common-sense’ and discrete institutional spheres of ‘economy’, ‘society’ and ‘environment’, an institutional constellation in which the ‘economy’ is usually afforded pre-eminence. Building on this, the paper further asks: why does the organization of society around the commodity form, and specifically around the generalization of the commodity form to labour-power that is the defining feature of capitalism, have the tendential effect of fragmenting, atomizing, and marginalizing social collectivities and cooperative behaviour? This question is answered through examination of the work of Polanyi and Marx, arguing that it is the latter who is best able to explain the nature and dynamics of capitalism, and its relationship to cooperative activity. The paper elaborates the Marxian approach and suggests strong linkages with the ‘radical’ fraction of the food sovereignty movement. The latter, like Marx, appears to invoke unconstrained cooperation as ‘actual’ autonomy; the paper asks what the political and ecological prerequisites for the realization of this social imaginary might be.
Rural Studies; Agroecology
Keywords: MARX; Karl; 1818-1883; agroecology; cooperation; food sovereignty; political ecology; rural studies

Karl Polanyi: A Life on the Left - Moravcsik, Andrew (Foreign Affairs, 2016)
Political Science
Keywords: DALE; Gareth; Karl Polanyi: A Life on the Left (Book); biography; book review; nonfiction; sociologists

Think tanks and the pressures for planning reform in England - Haughton, Graham; Allmendinger, Phil (Environment & Planning C: Government & Policy, 2016)
This article examines how advocacy think tanks have sought to influence the remaking of the English planning system. Pressure for planning reform has come particularly though not exclusively from the political right, which has sought to portray planning as a form of bureaucratic regulation, out of touch with the needs of modern, global economies and the needs of society. This research involved 27 interviewees, the majority of whom have worked in think tanks, whilst others worked in government or in advocacy and professional groups. We explore how despite years of critique and many reforms to the planning system, it is still portrayed as failing. Drawing on ideas around the experimental state, we seek to develop a better understanding of the dynamics behind the process of continuous calls for planning reform before turning to some of the implications for both planning and our understanding of how think tanks seek to influence policy.
Geography
Keywords: advocacy groups; environmental protection planning; experimental state; markets; planning reform; political reform; research institutes; think tanks

Moral economy: Rethinking a radical concept - Palomera, Jaime; Vetta, Theodora (Anthropological Theory, 2016)
This article argues that the original thrust of the moral economy concept has been understated and attempts to cast it in a new light by bringing class and capital back into the equation. First, it reviews the seminal works of Thompson and Scott, tracing the origins of the term. It deals with the common conflation of moral economy with Polanyi’s notion of embeddedness, differentiating the two concepts and scrutinizing the ways in which these perspectives have been criticized. Second, it dispels dichotomist conceptions separating economic practice from morality, or embedded configurations from disembedded ones. Against binary views of the market as a boundless realm penetrating previously untainted moral spheres, it posits that social reproduction is characterized by an entanglement of values, which can only be fully grasped by delineating the contours and characteristics of capital accumulation. Third, it contends that moral economy is a dynamic concept because it accounts for class-informed frameworks involving traditions, valuations and expectations. Finally, it argues that moral economy can enrich the concept of hegemony because it pays attention to the often-contradictory values that guide and sustain livelihood practices, through which cultural domination is reproduced or altered.
Anthropology
Keywords: SCOTT; James C.; THOMPSON; E.P.; capital; class; economics - moral & ethical aspects; embeddedness; hegemony; moral economy; saving and investment; social reproduction

Counterbalancing marketization informally: Georgia’s new-institutionalist reform and its discontents - Rekhviashvili, Lela (Debatte: Review of Contemporary German Affairs, 2016)
Discussing the case of institutional change and its discontents in the Georgian context, this article critically engages with one of the most influential perspectives on informal economic practices, namely the new institutionalist perspective. The examination of the responses to the new-institutionalist remedies reveals counterintuitive outcomes to allegedly successful market-enhancing reforms. The reforms were resisted and they failed to deliver the promise of improved entrepreneurial opportunities and eased social vulnerability. I suggest that the new-institutionalist prescriptions result in counterintuitive outcomes as they are based on two misleading assumptions. First, they read informal practices as a priori market-like and second, they see the transition to a market economy as a relatively harmonious process. I argue that, informal economic practices are not necessarily market-like, nor is the establishment of market-enhancing reforms uncontested by informally operating actors. Instead, the persons operating informally draw on non-commodified resources and suffer significant social and economic losses when the state-supported process of marketization deepens. The process of adjusting to marketization and coping with its costs inevitably involves elaboration of practices and interventions that defy and contradict the market logic. Precisely, this dismissal of the need for non-market-based solutions in current theory and practice leads to informalization of the resistance against marketization.
Political Science
Keywords: Eastern Europe; Georgia; Polanyian institutionalism; informal economic practices; informal sector (economics); marketization; markets; new-institutionalism; organizational change

Climate change and the welfare state? Exploring Australian attitudes to climate and social policy - Spies-Butcher, Ben; Stebbing, Adam (Journal of Sociology, 2016)
Despite growing evidence of significant impacts from human-induced climate change, policy responses have been slow. Understanding this policy inertia has led to competing explanations, which either point to the need to build a consensual politics separated from economic partisanship, or which encourage solidarities between environmental and social movements and issues. This article analyses a recent successful mobilisation, leading to the passage of the Clean Energy Act in Australia, to explore the relationship between attitudes to environmental and social protection, particularly among the core constituency in favour of stronger climate action. Using social survey data from the Australian Election Study, the article finds evidence of independent associations between prioritising environmental concerns and support for welfare state expansion, and a realignment of materialist and post-materialist values. This we argue is consistent with Polanyian analysis that posits a link between social and environmental causes based on resistance to commodification.
Sociology
Keywords: clean energy; climate policy; climatic changes - government policy; commodification; law and legislation; political attitudes; social policy; welfare state

How Will Capitalism End?: Essays on a Failing System - Streeck, Wolfgang (Verso Books, 2016)
The provocative political thinker asks if it will be with a bang or a whimperAfter years of ill health, capitalism is now in a critical condition. Growth has given way to stagnation; inequality is leading to instability; and confidence in the money economy has all but evaporated.In How Will Capitalism End?, the acclaimed analyst of contemporary politics and economics Wolfgang Streeck argues that the world is about to change. The marriage between democracy and capitalism, ill-suited partners brought together in the shadow of World War Two, is coming to an end. The regulatory institutions that once restrained the financial sector’s excesses have collapsed and, after the final victory of capitalism at the end of the Cold War, there is no political agency capable of rolling back the liberalization of the markets.Ours has become a world defined by declining growth, oligarchic rule, a shrinking public sphere, institutional corruption and international anarchy, and no cure to these ills is at hand.
Sociology; Political Science
Keywords: political science / globalization; political science / political economy; political science / political ideologies / democracy

Polanyi and Political Consumption: A Modern Theoretical Application of the Double Movement - Frank, Phillip M. (Society for Marketing Advances Proceedings, 2016)
There has been an increase in literature on a growing field recently termed, "Political Consumption" (Baumann et al., 2015). Political consumption is defined as the choice or avoidance of products or brands with the aim of changing ethically or politically objectionable institutional or market practices (Shah et al., 2007). The following paper posits a theoretical model for the conceptualization of political consumption. Specifically, the author presents Karl Polanyi and his "Double Movement" as the underpinning theoretical conceptualization of Political consumption. The author also proposes empirical research to test such a theoretical model.
Business; Marketing
Keywords: brand choice; branding (Marketing); consumer behavior; consumption (economics); double movement; political consumption; product management

Moving targets: Carbon pricing, energy markets, and social movements in Australia - Pearse, Rebecca (Environmental Politics, 2016)
Reporting on the origins and directions of social movement strategy on climate and energy issues in the last decade, the shifts in ‘climate movement’ practice are discussed using a neo-Polanyian account of the political economy of climate change combined with sociological analysis of the strategic decisions campaigners reported making. Since the mid-2000s, Australia’s climate movement has been engaged in three concurrent arenas of political contestation. The longest-standing arena of movement activity has been negotiations over climate policy. More recently, activists and communities are engaged in a struggle over the expansion of fossil fuels. A third contest has been waged over the present and future position of renewable energy technologies in Australia’s electricity market. In the wake of climate policy failure, energy campaigns have been deepened, and it seems that a broader energy justice agenda is being forged. New strategic dilemmas are visible in the field.
Environmental Studies; Education
Keywords: Australia; carbon pricing; climate policy; climatic changes; economics; energy industries; energy markets; fossil fuels; renewable energy sources; social movements

Toward a Polanyian network analysis: market and non-market forms of coordination in the rice economy of Vietnam - Prota, Laura (Journal of Economic Geography, 2016)
The study proposes a network-based methodology linking Polanyi's ideal types of coordination and deductive blockmodeling to identify different forms of coordination within an economy. Using the proposed methodology, the economy of rice in postsocialist Vietnam is interpreted as a double movement responding to market liberalization. Qualitative and relational data were collected from 323 households and firms in two communes of the Mekong River Delta of Vietnam. Results show that in one case markets and redistribution co-existed as competing forms of coordination, entailing different relations of production and labor conditions; while in the other they blended and constituted a hybrid house-holding system.
Geography
Keywords: Vietnam; Vietnam transition; blockmodeling; corporate governance; economic coordination; embeddedness; liberalization (finance); local governance; markets; networks; rice - economic aspects; social networks

Embeddedness and migrant tourism entrepreneurs: A Polanyian perspective - Su, Xiaobo; Chen, Zhigang (Environment and Planning A, 2016)
Tourism embodies flows of tourists, capital and information, as well as migration, including migrants who operate businesses. How do migrant entrepreneurs negotiate social ties and economic activities in their destinations? To answer this question, the paper draws on Polanyi’s work on embeddedness to explore migrant tourism entrepreneurs (MTEs) and their modes of integration in the practice of social and economic life. We argue that MTEs are situated in a complex matrix in which they must build economic connections with locals and government officials, yet maintain a respectful distance with local groups, and develop embedded ties with other fellow migrants and tourists. Embeddedness, juxtaposed with distance, indicates that in tourist destinations, mixed patterns of economic and social relations significantly influence MTEs’ social and economic life. A Polanyian perspective on embeddedness can provide useful theoretical tenets to understand entrepreneurial activities in a mobile world.
Geography
Keywords: Lijiang ancient town; embeddedness; migrant tourism entrepreneurs; social and economic life; tourism production system

Karl Polanyi and the Reality of Society - Behrent, Michael C. (History and Theory, 2016)
This essay reconsiders Karl Polanyi's famous thesis about the “embeddedness” of the economy through an examination of two recent books: For a New West, a collection of previously unavailable essays by Polanyi, and Fred Block and Margaret R. Somers's The Power of Market Fundamentalism: Karl Polanyi's Critique. The guiding thread of this analysis is the claim that a constant in Polanyi's thought was his belief in what he called “the reality of society,” that is, that society exists as a social fact over and above the individuals that constitute it. The essay begins by tracing Polanyi's intellectual development, drawing primarily on the essays found in For a New West. Polanyi's quest to reconcile individual freedom with social solidarity led him first, in the years between the First and Second World Wars, to embrace liberal socialism, before his readings in anthropology persuaded him that traditional economies “embed” the economy in social relations and that the nineteenth-century liberal project of a “disembedded” economy (through the so-called free market) is a departure from this anthropological norm. The essay then examines and questions Block and Somers's claim that Polanyi maintained that the economy is always “already embedded,” arguing notably that Polanyi believed that the advent of market society entailed an economy that was actually disembedded from social relations, not merely one that was re-embedded in an alternative set of institutions.
History
Keywords: already embedded; anthropology; capitalism; embeddedness; liberalism; markets; reality of society; socialism; society

'Socialist Accounting' by Karl Polanyi: with preface 'Socialism and the embedded economy' - Bockman, Johanna; Fischer, Ariane; Woodruff, David (Theory & Society, 2016)
Ariane Fischer, David Woodruff, and Johanna Bockman have translated Karl Polanyi's 'Sozialistische Rechnungslegung' ['Socialist Accounting'] from 1922. In this article, Polanyi laid out his model of a future socialism, a world in which the economy is subordinated to society. Polanyi described the nature of this society and a kind of socialism that he would remain committed to his entire life. Accompanying the translation is the preface titled 'Socialism and the embedded economy.' In the preface, Bockman explains the historical context of the article and its significance to the socialist calculation debate, the social sciences, and socialism more broadly. Based on her reading of the accounting and society that Polanyi offers here, Bockman argues that scholars have too narrowly used Polanyi's work to support the Keynesian welfare state to the exclusion of other institutions, have too broadly used his work to study social institutions indiscriminately, and have not recognized that his work shares fundamental commonalities with and often unacknowledged distinctions from neoclassical economics.
Sociology; Political Science
Keywords: Keynesian economics; Keynesianism; embeddedness; neoclassical economics; social accounting; socialism; socialist accounting; socialist calculation debate; welfare state

Polanyi, political-economic opportunity structure and protest: capitalism and contention in the post-communist Czech Republic - Císař, Ondřej; Navrátil, Jiří (Social Movement Studies, 2016)
Drawing on Polanyian logic, we focus on the gradual institutionalization of capitalism in the Czech Republic and the protests accompanying this process. We hypothesize that different configurations of political economy, or what we term the political economic opportunity structure, trigger different popular responses and are a potent indicator of expected protest forms. To analyze this we chose to carry out a country case study, in which many variables commonly associated with political mobilization, in particular the state’s institutional structure, are kept constant. By contrast, models of political economy vary over time, as a function of the extent and form of the international integration of capitalism. We focus on three configurations of political economy – national, globalized and austerity models – and for each one, identify the characteristics and mechanisms, i.e. concrete policy measures, that shape particular protest patterns in the context of our case study. In theoretical terms, this paper seeks to present one possible response, in this case a Polanyian response, to recent complaints about the disappearance of capitalism from social movement studies. At the same time, given the focus of this special issue, our goal is to analyze the current wave of anti-austerity protest that emerged in relation to what has been labelled the Great Recession.
Sociology; Economics
Keywords: Czech Republic; anti-austerity; economic protest; political economic opportunity structure; political opportunity structure; social movement studies

Economic Exchange: Interdisciplinary Conceptualizations for Management Applications - Das, Roshni (Vilakshan: The XIMB Journal of Management, 2016)
The concept of 'Economic Exchange', taken in the neoclassical economics sense, has traditionally yielded a unilateral direction for business and management studies, that of profit maximization. This paper argues that, the same, when conceptualized from a sociological and anthropological point of view in particular, taking theorization by Polanyi (1946), Weber (1978) and Zafirovski (2001) into cognizance, can generate many alternative and interesting directions. Illustrations for the same have been provided in the form of management applications. Some controversies in the lifecycle of the concept have been noted such as that of the 'rational' man or Homo Economicus, which eventually led to the emergence of socio-economics and the consequential paradigmatic realignments among scholars, as a rebuttal to the dominant paradox. We undertake a conceptual exploration and synthesis of the relevant trans-disciplinary literature. Future implications for discursive research in management are discussed.
Management Studies
Keywords: WEBER; Max; 1864-1920; ZAFIROVSKI; M.; anthropology; economic exchange; economic man; homo economics; homo economicus; industrial management; methodological indivisualism; profit maximization; socioeconomics

Re-embedding Financial Stakes within Ethical and Social Values in Socially Responsible Investing (SRI) - Revelli, Christophe (Research in International Business and Finance, 2016)
The aim of this study is to understand how the definition of ethics in finance has steered socially responsible investing (SRI) towards a financial approach where ethics is guided by finance. Following a critical perspective of historical and modern SRI, we advocate a reconceptualization of the SRI paradigm through a framework that re-embeds finance in ethical and social values according to Polanyi's theory of embeddedness. To conclude, we propose an SRI model where impact measurement and extra-financial performance guide investments.
International Business
Keywords: economic anthropology; economic sociology; embeddedness; general financial markets: general (includes measurement and data) G10; social and economic stratification; social finance; socially responsible investing

Formal Economy, Substantive Economy, and Economism - Sobel, Richard; Postel, Nicolas (Philosophy of the Social Sciences, 2016)
Polanyi analyzes the historical deployment of a “formal” economic science starting from the “market-scarcity-instrumental rationality triptych.” This triptych, and the knowledge associated with it, is shown to be more than merely a “substantial” economic science’s interest in the triptych “need-nature-institution.” While we must agree with Polanyi that economism is ill-suited to the first triptych, we hesitate to accept his suggested alternative, a heterogeneous mixture of naturalism and institutionalism, essentialism and historicism.
Sociology; Economics
Keywords: capital shortages; capitalism; economic systems; economism; essentialism (philosophy); formal economy; historicism; institutionalism (religion); profit; rationality; scarcity; substantive economy

Beyond prices: The cultural economy of water in the Cordillera highlands of Northern Luzon, Philippines - Abansi, Corazon L.; Doble, Maria Consuelo C.; Cariño, Jessica K.; Rola, Agnes C. (Asia Pacific Viewpoint, 2016)
This paper analyses how the economic actions of water distribution and exchange are embedded in the culture of indigenous communities in the Cordillera highlands of Northern Luzon, Philippines. Such actions are fundamental to water access and provisioning. Data was derived from a series of focus group discussions conducted with various water users, including households, farmers, enterprises and local government officials, and from upstream, midstream and downstream communities along the Balili River, a critical watershed in the Cordillera highlands. The study area exhibits a mix of livelihood systems and both formal and traditional institutions of decision-making. Recognising that water is both an economic and social good, this paper draws inspiration from Polanyi's concept of embeddedness. Cases of three communities suggest that water distribution and exchange are embedded in the community's socio-cultural spaces, but the extent of embeddedness declines as communities transform from subsistence to market-based economies. Embeddedness also determines value and availability of water. The paper contributes to the discourse on the cultural economy of water and provides direction on new modes of decision-making on river management that promise more inclusive, equitable and ecologically sustainable outcomes.
Economics
Keywords: Philippine Cordillera; cultural economy; embeddedness; water distribution and exchange

Regulating class in the neoliberal era: the role of the state in the restructuring of work and employment relations - Howell, Chris (Work, Employment & Society, 2016)
The article argues that, in the last three decades, states have become more preoccupied with, and interventionist in, the regulation of class relations in order to facilitate a broad liberalization of employment relations institutions. Drawing on insights from Regulation theorists and Karl Polanyi, the article examines the market-making role of states during periods of transition from one growth regime to another. The more prominent role of the state follows from the stickiness of institutions and the role that states can play in compensating workers from the consequences of liberalization. The article illustrates the argument with an examination of France and Sweden in the period since the early 1980s. For all their differences, in both cases substantial liberalization of employment relations institutions took place and in both cases, but for the state, the process of liberalization would have been either stymied or much more uneven than it was.
Political Science
Keywords: class; employment relations; liberalization; state

The failure of regulation: Work, environment and production at Taranto’s ILVA - Greco, Lidia; Chiarello, Franco (Economic & Industrial Democracy, 2016)
The article focuses on the case of the largest steel plant in Europe, located in Taranto (Italy), to argue that its current crisis is not simply dictated by technological or managerial failings. Rather, the article contends that its problems stem from a regulatory crisis and, specifically, from the failure of the deregulation model pursued after the industry’s process of privatization. Such a model has hinged upon the logic of a big private firm that, on the one hand, has sought to disembed itself from the socio-institutional context and, on the other, has set and followed its own rules with disruptive effects on the local society and environment, as well as on the plant’s economic viability. Such a model entered a crisis when the other socio-institutional actors started to react to the disastrous situation existing in Taranto. To use Polanyian language, a ‘double movement’ has emerged: disruptive pressures have triggered defensive reactions.
Political Science
Keywords: Taranto (Italy); economic democracy; employee ownership; employee participation in management; financial crises; financial crisis; industrial democracy; institutional change; privatization - Italy; sociology; technological innovations

The business of the Anthropocene? Substantivist and diverse economies perspectives on SME engagement in local low carbon transitions - North, Peter (Progress in Human Geography, 2016)
The involvement of private sector actors in low carbon urban transitions is a neglected element of geographical analysis. Drawing on Polanyian, cultural economic geographies and the non-capitalocentric ethics of JK Gibson-Graham’s diverse economies perspective, the paper engages with the wider literature on the engagement of small and medium enterprises (SMEs) in environmental action, corporate social responsibility and low carbon transitions to develop a substantivist account of the contribution of SMEs to local low carbon transitions. The paper argues that, contra formalist economic analyses of economic rationality, SME owners should not be thought of as uncritical profit maximizers but as actors in favour of positive low carbon futures. Thus the paper argues that Polanyian economic geographies and diverse economies perspectives, which rarely speak to each other, can be drawn together, and concludes with suggestions for future research.
Geography
Keywords: Polanyian geographies; carbon offsetting; cultrual geography; diverse economies; environmental protection; local business representation; local economic development; low carbon transitions; small business; social responsibility of business; substantivist

Karl Polanyi: The Hungarian Writings - Dale, Gareth (Oxford University Press, 2016)
The work of Karl Polanyi has gained in influence in recent years to become a point of reference to a wide range of leading authors in the fields of economics, politics, sociology, and social policy. The volume is a combination of reflections on, and assessment of, the nature of Polanyi's contribution and new strands of work, both theoretical and empirical, that has been inspired by Polanyi's insights. It gathers together the key contributions to the first ever workshop on the work of Karl Polanyi held in the United Kingdom. The workshop was opened by Kari Polanyi-Levitt, who also has written the Introductory Foreword to this book. Several of the contributions develop Polanyian ideas in relation to contemporary capitalism. However, in a critical spirit, other contributions in the volume substantially transform his concept 'instituted economic process' in considering a broad range of contemporary socio-economic change: markets for mobile telephony, call centre operations, and European labour markets.
Political Science
Keywords: history - modern; political history; political philosophy; political theory

Globalization and Its Countermovement: Marxian Contention or Polanyian Resistance? - Gemici, Kurtuluş; Nair, Manjusha (Sociology Compass, 2016)
This article surveys the scholarship on the countermovement against the diffusion of capitalism and market economy in the Global South. We identify two streams of analysis in the literature. On the one hand, scholars observe contentious politics instances where the spread of capitalist production relations enables the associational capacity and bargaining power of social classes. On the other hand, there are voluminous studies on contentious politics in the Global South where groups such as peasants, shopkeepers, and urban poor resist the intensification of the market economy. We use Beverly Silver's distinction between Marx-type and Polanyi-type protests, which focuses on how globalization makes and unmakes social groups, to unpack the heterogeneity of the impacts and experiences of globalization. We argue that although Silver's distinction is of great analytical value, there are strong warrants for separating the effects of the market economy from capitalism in studying contentious politics against globalization. Such an analytical strategy (i) expands the scope of the distinction between Marxian and Polanyian contention to social groups other than the working class and (ii) emphasizes that the roots of these struggles lie in the interconnected diffusion of capitalism and market economy.
Sociology
Keywords: Global South; MARX; Karl; 1818-1883; SILVER; Beverly; countermovement; global south; globalization

In search of Karl Polanyi's International Relations theory - Dale, Gareth (Review of International Studies, 2016)
Karl Polanyi is principally known as an economic historian and a theorist of international political economy. His theses are commonly encountered in debates concerning globalisation, regionalism, regulation and deregulation, and neoliberalism. But the standard depiction of his ideas is based upon a highly restricted corpus of his work: essentially, his published writings, in English, from the 1940s and 1950s. Drawing upon a broader range of Polanyi's work in Hungarian, German, and English, this article examines his less well-known analyses of international politics and world order. It sketches the main lineaments of Polanyi's international thought from the 1910s until the mid-1940s, charting his evolution from Wilsonian liberal, via debates within British pacifism, towards a position close to E. H. Carr's realism. It reconstructs the dialectic of universalism and regionalism in Polanyi's prospectus for postwar international order, with a focus upon his theory of 'tame empires' and its extension by neo-Polanyian theorists of the 'new regionalism and European integration. It explores the tensions and contradictions in Polanyi's analysis, and, finally, it hypothesises that the failure of his postwar predictions provides a clue as to why his research on international relations dried up in the 1950s.
Political Science
Keywords: CARR; Edward Hallett; 1892-1982; deregulation; international relations; liberalism; neoliberalism

Embedding Capital: Political-Economic History, the United States, and the World - Kramer, Paul A. (Journal of the Gilded Age & Progressive Era, 2016)
The article examines U.S. political and economical history in the context of its impact as well as influence to world affairs. Topics discussed include the Marxist's historical approaches to analysis of capital as in Karl Polanyi's take on American capitalism, "primitive accumulation" with regimes of commodification and the "new history of capitalism" hype. Also mentioned were transnational expansion of humanitarianism, international education sponsorship and Andrew Carnegie's philanthropy.
History
Keywords: United States - politics & government - history; capital; capitalism; economics - United States - history; embeddedness; humanitarianism

Brexit: Doom, or Europe’s Polanyi Moment? — Welcome to TheFamily - Colin, Nicolas (Medium, 2016)
N/A
Keywords: Brexit; entrepreneurship; fascism

The New Washington Consensus: Millennial Philanthropy and the Making of Global Market Subjects - Mitchell, Katharyne; Sparke, Matthew (Antipode, 2016)
This paper outlines the emergence of a New Washington Consensus associated with leading philanthropies of the new millennium. This emergent development paradigm by no means represents a historic break with the market rationalities of neoliberalism, nor does it represent a radical departure from older models of early 20th century philanthropy. Rather, it is new in its global ambition to foster resilient market subjects for a globalized world; and new in its employment of micro-market transformations to compensate for macro-market failures. Focusing on reforms pioneered by the new philanthropic partnerships in education and global health, the paper indicates how the targets of intervention are identified as communities that have been failed by both governments and markets. The resulting interventions are commonly justified in terms of “return on investment”. But the problems they target keep returning because the underlying causes of failure are left unaddressed.
Geography
Keywords: development; education; global health; millennial philanthropy; neoliberalism; philanthropy; triple movement

Expanding the labor theory of value - Collins, Jane (Dialectical Anthropology, 2016)
This paper revisits debates over the labor theory of value in the 1970s and 1980s and proposes an expansion and revision for the neoliberal era. It draws on three empirical cases of social movements grappling with contemporary changes in the societal division of labor and argues that they can best be understood as 'revaluation' projects seeking to bring recognition to aspects of the economy that are necessary for its long-term sustainability but are not 'counted' as important.
Anthropology
Keywords: division of labor; domestic labor; environment; feminism; labor theory of value; labour theory of value; neoliberalism; public sector; shareholder value; social movements; sustainability

Apple, Foxconn, and Chinese workers’ struggles from a global labor perspective - Pun, Ngai; Shen, Yuan; Guo, Yuhua; Lu, Huilin; Chan, Jenny; Selden, Mark (Inter-Asia Cultural Studies, 2016)
To enrich the discussion of global labor, between 2010 and 2016, we studied Apple’s value chain, Foxconn’s mode of labor control, and Chinese workers’ struggles. Through our fieldwork in China we also examined Apple’s and Foxconn’s responses to the spate of worker suicides, workers’ resistance, the activism of scholar and student groups, and transnational justice campaigns. We conclude with reflection on global labor studies in light of the debates between Karl Polanyi’s counter movement and Karl Marx’s class-based struggle.
Sociology; Asia Studies
Keywords: Apple; Apple Inc.; China; Chinese workers; Foxconn; Foxconn Technology Group (Company); MARX; Karl; 1818-1883; POLANYI; Karl; 1886-1964; countermovement; global labor studies; global labour studies; student and scholar activism; value chains; working class

Karl Polanyi: A Life on the Left - Dale, Gareth (Columbia University Press, 2016)
Karl Polanyi (1886–1964) was one of the twentieth century's most original interpreters of the market economy. His penetrating analysis of globalization's disruptions and the Great Depression's underlying causes still serves as an effective counterargument to free market fundamentalism. This biography shows how the major personal and historical events of his life transformed him from a bourgeois radical into a Christian socialist but also informed his ambivalent stance on social democracy, communism, the New Deal, and the shifting intellectual scene of postwar America.The book begins with Polanyi's childhood in the Habsburg Empire and his involvement with the Great War and Hungary's postwar revolution. It connects Polanyi's idealistic radicalism to the political promise and intellectual ferment of Red Vienna and the horror of fascism. The narrative revisits Polanyi's oeuvre in English, German, and Hungarian, includes exhaustive research in five archives, and features interviews with Polanyi's daughter, students, and colleagues, clarifying the contradictory aspects of the thinker's work. These personal accounts also shed light on Polanyi's connections to scholars, Christians, atheists, journalists, hot and cold warriors, and socialists of all stripes. Karl Polanyi: A Life on the Left engages with Polanyi's biography as a reflection and condensation of extraordinary times. It highlights the historical ruptures, tensions, and upheavals that the thinker sought to capture and comprehend and, in telling his story, engages with the intellectual and political history of a turbulent epoch.
History
Keywords: European history; biography; history - Europe / Austria & Hungary; history - United States / 20th Century; history - modern; history - modern / 20th Century; social science; sociology

The catastrophe of neo-liberalism Finance, emancipation and disintegration - Foster, Roger (Philosophy & Social Criticism, 2016)
My article provides a systematic interpretation of the transformation of capitalist society in the neo-liberal era as a form of what Karl Polanyi called ‘cultural catastrophe’. I substantiate this claim by drawing upon Erich Fromm’s theory of social character. Fromm’s notion of social character, I argue, offers a plausible, psychodynamic explanation of the processes of social change and the eventual class composition of neo-liberal society. I argue, further, that Fromm allows us to understand the psychosocial basis of the process that Polanyi calls cultural catastrophe. This requires an elucidation of the major social forces of financialization and emancipation which, I argue, proved to be important formative factors in the emergence of neo-liberal society. The cultural catastrophe of neo-liberalism concerns the working class, whose prevailing social character has become misaligned with the new expectations and requirements of neo-liberal society.
Philosophy
Keywords: FROMM; Erich; cultural catastrophe; emancipation; financialization; neo-liberalism; neoliberalism

The Commonalities of Global Crises: Markets, Communities and Nostalgia - Karner, Christian; Weicht, Bernhard (Springer, 2016)
Bringing together contributions from an international group of social scientists, this collection examines diverse crises, both historical and contemporary, which implicate market forces, widening inequalities, social exclusion, forms of resistance, and ideological polarisation. The Commonalities of Global Crises offers carefully researched case studies which stretch across large geographical distances- from Egypt to the US and from northern, central, eastern and southern Europe to South America- and covers timely issues including human rights, slavery, care, migration, racism, and the far right. The volume demonstrates that such different settings and diverse concerns are characterized by a common tension in which the crises that unfold around pressures of widening marketization and commodification are met by the (re)building or re-assertion of various communities, and competing politics of solidarity and nostalgia.
Sociology; Political Science
Keywords: business & economics / general; commodification; disembedding; double movement; economic theory; political science / general; social science / general

Karl Polanyi and twenty-first century socialism - Block, Fred (openDemocracy, 2016)
Polanyi’s views were the exact opposite of his contemporary, Joseph Schumpeter, who famously defined democracy as giving people a choice over which elite group would rule over them.
Sociology
Keywords: socialism

The Hill and Knowlton Affair and the Marketization of the First Gulf War. a Polanyian Perspective - Petre, Silviu Valentin (Proceedings of the Scientific Conference AFASES, 2016)
The 1990-1991 First Gulf War became a classic manual of PR or manipulation, depends on the terms one chooses. Within the whole manipulative framework, Hill and Knowlton, one of USA’ s foremost advertising brands played a pivotal, ripple-making role. With the money provided by Kuwaiti government in exile, H&K faked several testimonies according to which Saddam’s soldiers had been responsible of appalling deeds by pillaging Kuwaiti hospitals, where they stole incubators and left newborn babies to die. Thus, President Bush gained legitimacy in front of the US Congress and international fora to assemble a coalition of the willing to deal with Iraqi aggression. This article will not only dwell upon the abovementioned episode, but shall also sketch an explanatory framework using Karl Polanyi’s writings.
Defence Studies
Keywords: BUSH; George H.W.; Gulf War; HUSSEIN; Saddam; Hill and Knowlton Strategies (Company); POLANYI; Karl; 1886-1964 - political and social views; Persian Gulf War; 1991; manipulation; manipulative behavior; public opinion; public relations & politics

Quality Work and the Moral Economy of European Employment Policy - Bolton, Sharon; Laaser, Knut; Mcguire, Darren (JCMS: Journal of Common Market Studies, 2016)
Following a decade of radical economic and workplace restructuring, it is important to understand how state employment policies support or deny human flourishing. This article utilizes a realist document analysis approach and reviews European employment policy through a moral economy lens. It fuses different moral economy approaches, drawing together the work of Karl Polanyi and Andrew Sayer a multi-layered conceptual lens is offered that explores the tensions between a commodification of labour and human needs. A dominant market ideology is revealed, highlighting how quality work has been subsumed by the flexicurity agenda in the EU.
Business & Management
Keywords: European employment policy; dignity; employment; flexicurity; management studies; moral economy; quality work

Public Capital and the Post-Communist Welfare State: The Case of Poland - Rae, Gavin (Polish Sociological Review, 2016)
This paper provides an overview of some of the main theories of the welfare state. It builds upon Polanyi's theory of the double-movement and relates this to Bourdieu's concept of multiple capitals. It argues that the welfare state can be understood as a form of public capital, both in an economic and sociological sense. The welfare state emerges and is maintained due to a social countermovement that at least partly removes areas of socio-economic life out of commodity relations. In turn this creates public capital, which is both economic and social. In the post-Communist countries most of this public capital was created during a period when almost the whole of economic and social life was controlled by the state. Once the Communist system collapsed, so the accompanying policy of full-employment and system of social welfare organised through state enterprises disappeared. This was met with a large rise in unemployment and labour deactivation, meaning that many social benefits were created during the initial years of the transition. Also, the post-Communist systems inherited large amounts of public capital in the form of public services such as health and education. Through the example of Poland this paper analyses how this public capital was initially maintained and even developed during the early transition period, but then how a process of commodifying it was later begun.
Sociology
Keywords: BOURDIEU; Pierre; 1930-2002; Poland; capital; communism; countermovement; post-communism; public welfare; social movements; social policy; social services; welfare state

From Keynes to Piketty: The Century that Shook Up Economics - Haan, Peter de (Springer, 2016)
From Keynes to Piketty provides the reader with an accessible and entertaining insight into the development of economic thought over the past century. Starting with John Maynard Keynes's bestseller, The Economic Consequences of Peace (1919), and ending with Thomas Piketty's blockbuster, Capital in the Twenty First Century (2014), the author explains which dramatic political and economic events changed the way economists interpreted these events, and how they revolutionized the economic science.The book contains biographies of Keynes, Schumpeter, Galbraith, Hayek, Friedman, Hirschman, North, and Piketty, alongside others, and highlights their extraordinary lives and works, anecdotes about them, and their often sharp differences of opinion. Extensive summaries of their main works provide the interested scholar and student with an accurate presentation of their contents. A must-read for all those who wonder what happened to economics during the past century, and why.
Economics
Keywords: KEYNES; John Maynard; 1883-1946; PIKETTY; Thomas; business & economics; economic history

Polanyi’s ‘substantive approach’ to the economy in action? Conceptualising social enterprise as a public health ‘intervention’ - Roy, Michael J.; Hackett, Michelle T. (Review of Social Economy, 2016)
For several decades now, critical public health researchers have highlighted the deleterious effects that pursuing neoliberal policies can have on the ‘causes of the causes’ of poor health and upon growing health inequalities. This paper argues that the conceptual tools of Karl Polanyi can help lend particular insight into this issue. The specific example that this paper focuses upon is the ‘social enterprise’: a form of organisation that combines both social and business objectives. The paper explores, conceptually, whether social enterprises may have the potential to act as one component of a neo-Polanyian countermovement: helping to re-embed the economy back into society, and offering greater recognition for a more comprehensive and socially imbued concept of health. Importantly, this potential is critically examined in the context of neoliberal hegemony, where challenges to the status quo have regularly been met with assimilation, co-option and/or repression.
Sociology
Keywords: health inequality; public health; social enterprise; substantive approach

Bourgeois Equality: How Ideas, Not Capital or Institutions, Enriched the World - McCloskey, Deirdre N. (University of Chicago Press, 2016)
There’s little doubt that most humans today are better off than their forebears. Stunningly so, the economist and historian Deirdre McCloskey argues in the concluding volume of her trilogy celebrating the oft-derided virtues of the bourgeoisie. The poorest of humanity, McCloskey shows, will soon be joining the comparative riches of Japan and Sweden and Botswana. Why? Most economists—from Adam Smith and Karl Marx to Thomas Piketty—say the Great Enrichment since 1800 came from accumulated capital. McCloskey disagrees, fiercely. “Our riches,” she argues, “were made not by piling brick on brick, bank balance on bank balance, but by piling idea on idea.” Capital was necessary, but so was the presence of oxygen. It was ideas, not matter, that drove “trade-tested betterment.” Nor were institutions the drivers. The World Bank orthodoxy of “add institutions and stir” doesn’t work, and didn’t. McCloskey builds a powerful case for the initiating role of ideas—ideas for electric motors and free elections, of course, but more deeply the bizarre and liberal ideas of equal liberty and dignity for ordinary folk. Liberalism arose from theological and political revolutions in northwest Europe, yielding a unique respect for betterment and its practitioners, and upending ancient hierarchies. Commoners were encouraged to have a go, and the bourgeoisie took up the Bourgeois Deal, and we were all enriched. Few economists or historians write like McCloskey—her ability to invest the facts of economic history with the urgency of a novel, or of a leading case at law, is unmatched. She summarizes modern economics and modern economic history with verve and lucidity, yet sees through to the really big scientific conclusion. Not matter, but ideas. Big books don’t come any more ambitious, or captivating, than Bourgeois Equality. KM - Part IV heavily engages with Polanyi's ideas, including embeddedness
Economics; Political Science
Keywords: Europe; business & economics; economic history; embeddedness; history; political science; political theory; social science

The Great Acceleration: An Environmental History of the Anthropocene since 1945 - McNeill, J. R. (Harvard University Press, 2016)
The pace of energy use, greenhouse gas emissions, and population growth has thrust the planet into a new age—the Anthropocene. Humans have altered the planet’s biogeochemical systems without consciously managing them. The Great Acceleration explains the causes, consequences, and uncertainties of this massive uncontrolled experiment.
History; Political Science
Keywords: anthropocene; history / modern / 20th Century; history / world; nature / environmental conservation & protection; political science / public policy / environmental policy

England's Great Transformation: Law, Labor, and the Industrial Revolution - Steinberg, Marc W. (University of Chicago Press, 2016)
With England’s Great Transformation, Marc W. Steinberg throws a wrench into our understanding of the English Industrial Revolution, largely revising the thesis at heart of Karl Polanyi’s landmark The Great Transformation. The conventional wisdom has been that in the nineteenth century, England quickly moved toward a modern labor market where workers were free to shift from employer to employer in response to market signals. Expanding on recent historical research, Steinberg finds to the contrary that labor contracts, centered on insidious master-servant laws, allowed employers and legal institutions to work in tandem to keep employees in line. Building his argument on three case studies—the Hanley pottery industry, Hull fisheries, and Redditch needlemakers—Steinberg employs both local and national analyses to emphasize the ways in which these master-servant laws allowed employers to use the criminal prosecutions of workers to maintain control of their labor force. Steinberg provides a fresh perspective on the dynamics of labor control and class power, integrating the complex pathways of Marxism, historical institutionalism, and feminism, and giving readers a subtle yet revelatory new understanding of workplace control and power during England’s Industrial Revolution.
History; Economics; Sociology
Keywords: business & economics / economic history; economic history; history / Europe / Great Britain; history / general; industrial revolution; social science / sociology / general

For real: land as capital and commodity - Christophers, Brett (Transactions of the Institute of British Geographers, 2016)
With the aim of helping to revivify a stalled geographical literature on the place of land in capitalist political economies, this article presents a critique of the popular idea that land can be usefully conceptualised as a ‘fictitious’ form of capital or commodity. The critique is based primarily on a close and critical consideration of the grounds on which the identifiers and theorists of such fictitiousness – Marx/Harvey in the case of capital, Polanyi in the case of the commodity – distinguished it from ‘real’ variants. Those grounds, the article argues, are tenuous. And, far from disabling us, treating land as no more or less real than other forms of capital and commodity can empower us in productively revisiting and centring the question of land's political economy – a crucial undertaking in a world where the materiality of land to social relations is writ increasingly large.
Geography
Keywords: MARX; Karl; 1818-1883; capitalism; economic geography; fictitious capital; fictitious commodities; fictitious commodity; land; political economy; social economy

Fair trade certification as oversight: an analysis of fair trade international and the small producers' symbol - Clark, Patrick; Hussey, Ian (New Political Economy, 2016)
In this article we analyse Fair Trade as a form of non-state regulation, building on the literature on the internal politics and governance of Fair Trade International (FTI) certification. We focus on recent developments in the FTI certification system, including the split of Fair Trade USA from FTI and the emergence of the Small Producer's Symbol (SPP) as an alternative to FTI certification. We highlight the role of the three regional Producer Networks, in particular the Latin American Producer Network, the CLAC, in the politics and governance of the FTI system. In order to analyse these issues we employ an alternative reading of Karl Polanyi's work in relation to Fair Trade. We problematise the claim made by some in the literature that FTI certification is an example of Polanyi's concept of re-embedding. Instead, we draw on Polanyi's concept of oversight to analyse Fair Trade certification. We argue that the emergence of the SPP out of the CLAC shows promise for being a mechanism of oversight more reflective of Polanyian re-embedding than FTI certification. We also emphasise how the growth of the SPP and the pressure from the Producer Networks have prompted governance reform within the FTI system.
Political Science; Sociology
Keywords: Canada; Carleton University; European Union countries; certification; economic conditions; fair trade; financial crises; financial crisis; governance; liberalization (finance); municipal services; producer networks; small producers; unfair competition

Polanyian Pathways: A review of The Power of Market Fundamentalism: Karl Polanyi’s Critique by Fred Block and Margaret R. Somers and For a New West: Essays, 1919–1958 by Karl Polanyi; edited by Giorgio Resta and Mariavittoria Catanzariti - Peck, Jamie (Economic Geography, 2016)
Geography
Keywords: BLOCK; Fred; CATANZARITI; Mariavittoria; For a New West: Essays 1919-1958 (Book); POLANYI; Karl; 1886-1964; RESTA; Giorgio; SOMERS; Margaret R.; The Power of Market Fundamentalism: Karl Polanyi's Critique; The (Book); book review; nonfiction

Neoliberalism, Polanyi's Protective Response, and Veblenian Waste - Wrenn, Mary V. (Journal of Economic Issues (Taylor & Francis Ltd), 2016)
As capitalism unfolds, continual technological advance – in combination with the relentless accumulation imperative – serves to amplify material progress. The expanding economic sphere begins to pervade the everyday lives and thinking of the individual. The institutionalization of the market fundamentally changes the structure of society and, in so doing, fundamentally changes the institutional structure through which individuals are socialized. The social dislocation generated therein prompts Karl Polanyi's protective response. Despite this market intensification, the existence of the economic surplus undermines the syllogistics of market-determined pricing. Evidence of the economic surplus and Veblenian waste as well as of the fact that the competitive law of value is not operable under neoliberalism is found in the lobby industry and campaign contributions. This research seeks to explicitly connect the concepts of Polanyi's protective response with Veblenian waste and the economic surplus in order to better understand how the irrational system of neoliberalism continues to evolve.
Sociology; Economics
Keywords: Veblen; capitalism; economic sociology; economic surplus; institutional economics; neoliberalism

Saving the Commons in an Age of Plunder - Batt, H. William (American Journal of Economics and Sociology, 2016)
Land ownership, as commonly understood today, originated with the enclosure movement during the English Tudor era almost four centuries ago. Karl Polanyi referred to this “propertization” of nature as the “great transformation.” That land, water, and air was a social commons is now archaic and forgotten, and with it the classical economic concept of rent, which was, in theory, once paid to royalty as the earth's guardian. Garrett Hardin's article, “The Tragedy of the Commons,” raised alarm about the abuse and loss of this realm, and he recommended constraints and privatization to prevent this. Most people view titles to landed property much as they do their household goods, but Henry George saw that the earth should be seen as a common resource and its value taxed to benefit everyone. This would restore economic equilibrium to market exchanges and pay for government services. The capture of natural resource rents can supplant taxes on wages and capital goods, and it comports with all textbook principles of sound tax theory. This policy can be the modern replacement for the commons, and implementing resource rent capture is both economically and technically feasible.
Economics; Sociology
Keywords: commons; propertization of nature

Beyond the Minsky and Polanyi Moments - Gemici, Kurtuluş (Politics & Society, 2016)
The period of very high foreclosure rates sets the 2007–8 financial meltdown apart from similar banking crises fueled by asset price booms. Why did the 2007–8 meltdown lead to a prolonged foreclosure crisis? Through a theoretical perspective built on Minsky’s financial instability hypothesis, Polanyi’s ideas about adverse consequences of commodity fiction, financialization of homes, and institutional coupling, I argue that commodifying houses as financial assets exposed mortgage loan holders to price fluctuations originating in capital markets and elevated their risk of default. I show how increased exposure to price fluctuations followed from the tight coupling between U.S. housing and capital markets, a coupling that resulted directly from the rising preponderance of securitization in U.S. housing finance. I provide further evidence from countries where housing finance was tightly coupled with capital markets (Iceland and Ireland) to countries where housing finance did not rely dominantly on capital markets (Canada and the Netherlands).
Sociology
Keywords: MINSKY; Hyman; United States; asset-backed financing; economic aspects; financial instability; financialization; foreclosure; great recession; housing foreclosures; institutional coupling; recessions - 2008-2013; securitization

The New Urban Fiscal Crisis - Kirkpatrick, L. Owen (Politics & Society, 2016)
Numerous U.S. cities suffered immense fiscal strain following the subprime mortgage crisis and financial crash of 2007–8. Diminished revenues, tightened credit, and speculative financing that went bad in the aftermath fueled widespread fiscal distress on the local scale. Although the current moment resembles fiscal crises that crested in cities in the 1970s–90s, two factors distinguish the current period. First, municipal affairs have become thoroughly financialized—dominated by speculative securities and volatile debt arrangements—such that local crisis can no longer be understood apart from financial market instability. Second, local fiscal politics have become increasingly removed from democratic oversight and control. This de-democratization hinders the capacity of political communities to reregulate markets and rebuild urban communities. An analytic model derived from the work of Hyman Minsky and Karl Polanyi emphasizes how cities become ensnared in a “financial instability” cycle and how communities seek to protect themselves by way of the “double movement.”
Sociology
Keywords: Chicago; Detroit; MINSKY; Hyman; United States - economic conditions; de-democratization; financialization; municipal bonds; municipal finance; recessions - 2008-2013; urban fiscal crisis

Countermovement, Neoliberal Platoon, or Re-Gifting Depot? Understanding Decommodification in US Food Banks - Lindenbaum, John (Antipode, 2016)
In this paper, I explore the decommodification that takes place in US food banks. I argue that food banks are neither Polanyian countermovements re-embedding the market in society nor tiny platoons of neoliberalism that advance market relations and state withdrawal. Rather, food banks are best understood as re-gifting depots that are part of the capital accumulation process. Recent scholarship on primitive accumulation, the disarticulations approach, and waste suggests that the devaluation of food products and the exclusion of human labor are everyday elements of capitalism. I conclude by examining the potential for progressive politics in US food banking.
Geography
Keywords: Polanyi - political & social views; Supplemental Nutrition Assistance Program (U.S.); United States Deptartment of Agriculture; commodification; decommodification; disarticulation; equality - social aspects; food banks; food security; primitive accumulation; re-gifting depot; waste

The Copenhagen Turn in Global Climate Governance and the Contentious History of Differentiation in International Law - McGee, Jeffrey; Steffek, Jens (Journal of Environmental Law, 2016)
The 2009 Copenhagen Accord marked a significant shift in global climate governance which has been substantially adopted in the 2015 Paris Agreement. At Copenhagen, binding targets for states to reduce emissions were replaced by voluntary pledges. We argue that the Polanyian 'double movement' offers a useful lens to understand the Copenhagen shift in global climate governance as part of ongoing contestation in the international law system between principles of economic liberalisation and redistributive intervention. In the second half of the 20th century, redistributive design of international legal institutions became evident in a number of issue areas including trade law, oceans law and the seminal climate treaties. However, there has been ongoing US lead opposition to 'redistributive multilateralism' (RM), particularly over the last decade of climate negotiations. The Copenhagen model of voluntary pledges, therefore, needs to be viewed as an outcome of this opposition to RM and a related weakening of differentiation in international environmental law.
Law; Environmental Studies
Keywords: Copenhagen; Copenhagen Accord; UNFCCC; climate change; differentiation of duties; environmental justice; environmental law; international cooperation; international law; political economy; regime design

Economy, Society and Earth in Polanyian and Wild Law Perspectives on Environmental Regulation: To Perform a Double or Triple Movement? - Pontin, Ben (Journal of Environmental Law, 2016)
Law; Environmental Studies
Keywords: BURDON; Peter D.; HAINES; Fiona; LANGE; Bettina; MALONEY; Michelle; Regulatory Transformations: Rethinking Economy-Society Interactions (Book); THOMAS; Dania; Wild Law: In Practice (Book); book review; double movement; environmental law; nonfiction; triple movement

Revisiting Free Market Utopia: A Hayek-Polanyi Reminder - Usenmez, Ozgur; Duman, Levent (Journal of Economic and Social Thought, 2016)
As pundits discuss the causes and results of the 2008 financial crisis and ensuing Great Recession, economists of various strands–led mainly by Keynesians–are slowly beginning to question the supposed wisdom of unfettered markets. Since Keynesian-liberal disputes revolve around the symptoms of the crisis rather than the historical and structural features of market economies, we thought that a Hayek-Polanyi comparison would be a timely intervention in order to understand the real nature of the subject. This comparison may also pave the way for the creation of an alternative to the vagaries of unfettered markets.
Political Science
Keywords: Austrian; HAYEK; Friedrich A. von (Friedrich August); 1899-1992; Keynesian; Keynesianism; business fluctuations; cycles; evolutionary; financial crises; financial markets; financial markets and the macroeconomy; general aggregative models: Keynes; history of economic thought: individuals; institutional; post-Keynesian

Governing by Panic - Woodruff, David M. (Politics & Society, 2016)
The Eurozone’s reaction to the crisis beginning in late 2008 involved not only efforts to mitigate the arbitrarily destructive effects of markets but also vigorous pursuit of policies aimed at austerity and deflation. To explain this paradoxical outcome, I build on Karl Polanyi’s account of a similar deadlock in the 1930s. Polanyi argued that a society-protecting response to malfunctioning markets was limited under the gold standard by the prospect of currency panic, which bankers used to push for austerity, deflationary policies, and labor’s political marginalization. I reconstruct Polanyi’s “governing by panic” theory to explain Eurozone policy during three key episodes of sovereign bond market panic in 2010–12. By threatening to allow financial panics to continue, the European Central Bank promoted policies and institutional changes aimed at austerity and deflation, limiting the protective response. Germany’s Ordoliberalism, and its weight in European affairs, contributed to the credibility of this threat.
Political Science
Keywords: European Central Bank; Eurozone; Eurozone crisis; Eurozone debt crisis; depressions (economics) - 1929; economic conditions; euro; governing by panic; ordoliberalism

The new agrarian double movement: hegemony and resistance in the GMO food economy - Carroll, Myles (Review of International Political Economy, 2016)
This paper draws on the work of Antonio Gramsci and Karl Polanyi in analyzing the consequences of legal regimes that regulate genetically modified foods. Against the tide of neoliberalism, a binding, precautionary agreement over trade in genetically modified organisms (GMOs) has emerged through the Cartagena Protocol on Biosafety. This Protocol exemplifies what Polanyi termed the ‘self-protection of society,’ the second phase of his double movement. The Protocol's final form was a product of European governments’ responses to public concerns over the potential environmental and health impacts of GMOs in an unregulated global economy. This ‘self-protective’ turn has been manifest at regional and national scales, including in Australia. Drawing on Gramsci, I argue that this unlikely turn emerged in the context of shifting public opinion, effective anti-GMO activism, and alternative discursive framings. It took hold with European publics and governments, generating the relations of force needed to become the hegemonic framing of GMOs globally. The objectives of this paper are thus to demonstrate how a double movement has occurred in the regulation of GMOs and to use Gramsci's relations of force to explain how this double movement has nonetheless failed to challenge the underlying neoliberal basis of GMO agriculture as it exists today.
Political Science
Keywords: Australia; GMOs; agriculture - Australia; biosafety; double movement; economics; hegemony; international political economy; law; political economy; relations of force; transgenic organisms

Orientating disability studies to disablist austerity: applying Fraser’s insights - Dodd, Steven (Disability & Society, 2016)
Many disabled people in Britain have experienced profound challenges brought about by a government policy programme characterised by ‘austerity’. Drawing on the work of Fraser and Polanyi, this article explores new ways in which disability studies can become theoretically orientated to the task of explaining and challenging what has become an issue of overbearing importance for many disabled people. It is argued that Fraser’s notion of bivalency encapsulates the combination of cultural and economic challenges which characterise ‘disablist austerity’. Fraser’s development of Polanyi’s work is used to argue that disability studies should be orientated to large-scale economic challenges as well as cultural and discursive concerns that are more often the object of study in the field.
Health Studies; Disability Studies
Keywords: Great Britain; austerity; budget; conceptual structures (information theory); culture; disability studies; disablism; government policy; marketisation; people with disabilities - psychology; practical politics; public welfare; recognition; redistribution; research methodology; social justice; socioeconomic factors; triple movement

A Concept of Eurasia - Hann, Chris (Current Anthropology, 2016)
To imagine Europe and Asia as constituting equivalent "continents" has long been recognized as the ethnocentric cornerstone of a Western, or Euro-American, world view. The amalgam Eurasia corrects this bias by highlighting the intensifying interconnectedness of the entire landmass in recent millennia. This article builds on the work of Jack Goody and others to analyze the unity-in-civilizational-diversity of the Old World. It draws on the substantivist economic anthropology of Karl Polanyi to postulate continuities between ancient ideals of economic embeddedness in the agrarian empires and various forms of socialism in the twentieth century. Today, when the human economy everywhere is again exposed to the domination of the market, the Eurasian dialectic has universal relevance. However, recognition and realization of pan-Eurasian affinities continues to be impeded by geopolitics, and sociocultural anthropology has a long way to go to overcome its Atlantic bias.
Anthropology
Keywords: Eurasia; GOODY; Jack; 1919-2015; economic anthropology; ethnocentrism; geopolitics; socialism; substantivist

The Labor of Informational Democracy: A Library and Information Science Framework for Evaluating the Democratic Potential in Socially- Generated Information - Cope, Jonathan (Progressive community action: Critical theory and social justice in library and information science, 2016)
This essay outlines a framework that LIS can use to analyze socially-generated information. The proposed evaluative framework involves three democratic horizons of analysis: the level of access, the level of production, and the level of communicative speech. This inquiry synthesizes the political economy of communication/librarianship, autonomist Marxist insights about the dematerialization of labor in late capitalism, and the concerns of contemporary democratic theory. The essay concludes with a set of proposals for LIS to pursue research and policies that use a critical theoretical framework linking the realm of production (i.e., labor) with communicative democracy.
Library and Information Science; Information Studies
Keywords: MARX; Karl; 1818-1883; dematerialization of labor; informational democracy; late capitalism

Towards Another 'Great Transformation' - Mkandawire, Thandika (Africa Insight, 2016)
As Karl Polanyi indicates in the 'Great Transformation',1'the so-called self-regulating markets cannot exist for any length of time without destroying human society'. Three 'Great Transformations' have taken place. The first occurred in Europe at a time when it was widely believed that markets were nature's way of managing exchange in an efficient way and that interference in the workings of the market, as Adam Smith argued, was not only artificial, but against the laws of God.2 The second was about society's reaction in defending itself against the ravages of the market. The third was when neoliberalism launched a counter-movement that gave the market primacy. This paper argues that the assumption that the self-regulation expected from 'corporate social responsibility', or the instinct for self-preservation, would replace the state, had failed disastrously. The neoliberal model is therefore in trouble. It is important to contemplate a new global order that will be built on and facilitate social orders that are developmental, socially inclusive and democratic - which will be the fourth 'Great Transformation'. As the paper argues, there are two imperatives: the first imperative would be the creation of global institutions that would ensure that commitments to justice, equality and democracy are translated into global and national policies; and the second one would be the intellectual and ideological challenge of the views and discursive practices that, all too often, fetishised globalisation into some exogenous force that ineluctably imposes its laws on the human race.
Economics; Development Studies
Keywords: Africa studies; Europe; democracy; economic conditions; humanism; justice administration; socioeconomics

Organic farm volunteer tourism as social movement participation: a Polanyian political economy analysis of World Wide Opportunities on Organic Farms (WWOOF) in Hawai‘i - Mostafanezhad, Mary (Journal of Sustainable Tourism, 2016)
In recent years, Karl Polanyi's concept of the “double movement” has been resurrected to describe growing international resistance to neoliberal global capitalism. The double movement originally referred to counter-movements for social protection against the 19th and early 20th century laissez-faire market. Today, it describes the growth of new social movements which often resist neoliberal economic practices and ideologies. Drawing on Polanyi's concept of the double movement and on recent work on neoliberalism and new social movements, this article examines farm hosts' motivations for participation in World Wide Opportunities on Organic Farms (WWOOF). It argues that farm hosts tend to articulate their motivations as an attempt to proclaim solidarity with organic, spiritual, and educational new social movement agendas. It describes how a loosely articulated organic identity converges around three corollaryprotective counter-movements: organic food production and consumption, spirituality, and alternative education, exploring the creative ways people are resisting neoliberal capitalism at the intersection of alternative tourism and organic agriculture. Yet, despite hosts' intentions, the article illustrates how new social movement participation through WWOOF is in constant tension with the neoliberal agrarian and tourism marketplace in which it operates, as well as the perhaps unforeseen limits of its radical horizon.
Geography
Keywords: POLANYI; Karl; 1886-1964; agri-tourism; capitalism; critical theory; culture change; farm tourism; geography; neoliberalism; organic farming; sustainability; sustainable tourism; volunteer tourism

Market Reforms and Water Wars - Simmons, Erica S. (World Politics, 2016)
Responses to the imposition of market-oriented economic policies have varied. This article asks two questions: (1) How can we better understand when marketization will or will not prompt resistance? And (2) when people do mobilize, why are some movements broad-based while others draw on particular segments of society? The author argues that these questions can best be answered by focusing not only on the political contexts and resources available to potential social movements, but also on what is perceived to be at stake during marketization. These perceptions influence mobilization processes and the kinds of groups available for mobilization. When people understand markets as threatening to material wellbeing, as well as to widely shared community relationships, understandings, and commitments, heightened feelings of group belonging can contribute to broad-based mobilization. The author develops this argument through analysis of the broad-based, widespread movement that emerged to protest water privatization in Cochabamba, Bolivia, in 1999 and 2000. In the context of a history of agriculture, irrigation, drought, and conflict, water helped to produce and reproduce imagined communities of nation, region, and ethnic group, as well as quotidian communities revolving around the routine production and consumption of water. These meanings help to explain the dynamics of the resistance that emerged.
Political Science
Keywords: Latin America; marketization; political science; social movements; water wars

Ireland, Small Open Economies and European Integration: Lost in Transition - Begg, David (International Political Economy Series., 2016)
Presents a development model for the recovery of the Irish polity post-2008 financial crisis and traces and compares the evolution of the development models of Finland, Denmark, the Netherlands, and Ireland from 1987 to 2012, considering how those four countries managed the process of Europeanization. Explores the core Polanyian tension between markets and social protection, with particular reference to the capacity of selected small, open economies to manage that tension as compared with Ireland. Discusses the world of Peter J. Katzenstein–the major historical events that contributed to the formation of the polities of Denmark, Finland, the Netherlands, and Ireland, as well as how the development models evolved as European integration intensified; 1994-2001–the age of employment miracles; 2001-08–European integration intensifies; going beyond 2008–coping with the crisis; and unpacking Ireland's polity from a new institutionalist perspective. Begg is Director of the Think Tank for Action on Social Change and former General Secretary of the Irish Congress of Trade Unions. Bibliography; index.
Economics
Keywords: current heterodox approaches: historical; economic integration; evolutionary; heterodox economics; institutional; international institutional arrangements; international political economy; open economy macroeconomics; political processes: rent-seeking; lobbying; elections; legislatures; social protection; voting behavior

The contradictory logics of financialization: Bringing together hyman minsky and Karl Polanyi - Block, F. (Politics and Society, 2016)
This introduction explains the logic of bringing together the perspectives of Hyman Minsky and Karl Polanyi to analyze processes of financialization. Although Minsky and Polanyi have very different intellectual trajectories, there are important complementarities in their approaches. The introduction also explains the focus of the three papers in this special section written by Kurtuluşc Gemici, Lucas Kirkpatrick, and David Woodruff. © 2015 SAGE Publications.
Sociology
Keywords: MINSKY; Hyman; finance; financial crises; financial crisis; financialization; political economy; speculation

Human growth and avoiding European disintegration: lessons from Polanyi - Buzaglo, Jorge (real-world economics review, 2016)
Many economists, including mainstream economists, have declared the necessity of an ambitious public investment program for Europe. The continuation of the present laissez-faire and austerity approach, they say, will deepen the dissatisfaction of European peoples with the European project. In effect, in the absence of inspiring progressive alternatives, there is the real prospect of nationalistic reactions everywhere, with fragmentation and the end of the EU (or even worse) as a consequence. At the bottom of EU-fatigue there is dissatisfaction with the present economic paradigm, which implies social and economic strain and stagnation for a large majority, and growing wealth and privilege for a tiny minority (the “one percent”). A new social and economic paradigm should be necessary to reverse the negative and dangerous trends that the now more than 30 years old neoliberal paradigm has implied. To be effective, a new social and economic paradigm should underlie the new, ambitious European investment program. The guiding general idea of such a new, hopeful paradigm and program should be the idea of human growth. Human growth can be understood as the growth of human capabilities — the all-round development of individuals and societies. The paper summarizes a dynamic simulation model for the efficient allocation of investment. Investment efficiency is understood in the sense of the intersectoral allocation of investments being able to fulfil desired patterns of capability growth. That is, efficient investment programs are those that maximize the capacity of the production system — and in general, the socioeconomic system — of generating human growth.
Economics
Keywords: European Union; human growth

Reconstructing Karl Polanyi - Dale, Gareth (Pluto Press, 2016)
Karl Polanyi was one of the most influential political economists of the twentieth-century and is widely regarded as the most gifted of social democrat theorists. In Reconstructing Karl Polanyi, Gareth Dale draws upon primary sources archived in the countries that Polanyi called home—Hungary, Austria, Britain, the United States, and Canada—to provide a sweeping survey of his contribution to the social sciences. Polanyi’s intellectual and political outlook can best be summarized through paradoxical formulations such as ‘romantic modernist’, ‘liberal socialist’, and ‘cosmopolitan patriot.’ In exploring these paradoxes, Dale excavates and reconstructs Polanyi’s views on a range of topics that have been neglected in the critical literature, including Keynesian economic policy, the evolution and dynamics of Stalin’s Russia, regional integration, and McCarthyism. He reinterprets Polanyi’s philosophy of history, his theory of democracy, and his economic historiography of Ancient Greece and Mesopotamia, and guides readers through Polyani's critical dialogue with Marxism. While the central threads and motifs of this study are intellectual-historiographical in nature, Dale also critically analyzes the views of Polanyi and his followers on issues of pressing present-day relevance, notably the clash between democracy and capitalism, and the nature and trajectory of European unification.
Political Science
Keywords: political theory; social theory

Treble Troubles? Marketization, Social Protection and Emancipation Considered Through the Lens of Slavery - Davidson, Julia O’Connell (The Commonalities of Global Crises, 2016)
This chapter considers white European and American thinking on transatlantic slavery historically and, more briefly, in relation to today’s antislavery movement. Combining historical longue durée and a critical engagement with Nancy Fraser’s neo-Polanyian position, O’Connell Davidson shows that abolitionists were, and are, hard to fix as proponents of either market freedom or social protection, or indeed of ‘emancipation’. The postabolition experience of freed slaves shows that marketization, social protection and emancipation are not fully disarticulable political forces, suggesting that the idea of the ‘triple movement’ may be less useful for those committed to a politics of nondomination than it may initially appear.
Sociology; Political Science
Keywords: economics; public choice; slavery; social choice; social inequality; social protection; social structure; triple movement; welfare economics

Domesticating the market: moral exchange and the sharing economy - Fitzmaurice, Connor; Ladegaard, Isak; Attwood-Charles, William; Cansoy, Mehmet; Carfagna, Luka; Schor, Juliet; Wengronowitz, Robert (Under review at Socio-Economic Review, 2016)
The sharing economy has generated enormous excitement with its promise of transforming work and consumption through technology and novel socio-economic relations. However, critics see the phenomenon as a further development of neoliberalism. Platforms such as Airbnb and TaskRabbit, monetize a previously uncommodified realm of life via renting of bedrooms, possessions, space and labor time. In this paper, we analyze the meanings and attitudes of sharing economy participants. On the basis of 100 interviews in two for-profit and three not-for-profit sites, we find that most see the sharing economy as an opportunity to build a radically different market, from the bottom up. They are critical of the neoliberal market order, and envision an economy of personalized exchanges that are morally attuned, based on ideals of community, and that help them achieve creative and financial autonomy in their working lives. To our respondents, the sharing economy is an opportunity to domesticate the market.
Sociology
Keywords: domestic production; economic sociology; hostile worlds; markets; morality; neoliberalism; sharing economy

Social Quality - Herrmann, Peter (International Journal of Social Quality, 2016)
A fundamental methodological problem is the relevance of an antagonism of capitalism. This needs to be classified in light of the developmental stage of the means of production: far too little attention is paid to the contradictory character of individualization and socialization. This brings us to Karl Polanyi's main argument of disembedding. He also deals with a shift from the socially integrated (and dependent) individual to the utilitarian market citizen. The French regulationist theory offers a major step toward understanding new forms of societal embedding linked to this "new personality." It will also allow us to move beyond the misleading juxtaposition or dichotomization of individualization-socialization. Investigating five major tensions, it ventilates the possible meaning of the digital revolution and the challenges for monitoring development. The main aim of the article, however, is to bring the economy back in and to go beyond the traditional duality between economics and politics.
Economics
Keywords: capitalism; change; development; disembedding; economics; economics and social science; economy & society; social quality; social sciences; theory of regulation; work

Karl Polanyi for President - Iber, Patrick; Konczal, Mike (Dissent Magazine, 2016)
Are you a Bernie Sanders supporter? Chances are you'll like Karl Polanyi, too. An explainer.
N/A
Keywords: Great Transformation; The (Book); SANDERS; Bernie

The Methodology of Polanyi's Great Transformation: Commentary - Mayhew, Anne (Economic Thought, World Economics Association, 2016)
A commentary on Asad Zaman's paper “The Methodology of Polanyi's Great Transformation”
Economics
Keywords: ZAMAN; Asad; capitalist systems; economic methodology; economic thought; history of economic thought; political economy

Distribution-Led Growth in the Long Run - Nikiforos, Michalis (Review of Keynesian Economics, 2016)
This paper examines the long-run fluctuations in growth and distribution through the prism of wage- and profit-led growth. It argues that the relation between distribution of income and growth changes over time and proposes an endogenous mechanism that leads to fluctuations between wage- and profit-led periods. The ephemeral character of distribution-led regimes needs to be taken into account when someone estimates empirically the effect of a change in distribution on utilization and growth. The model is a linear version of Goodwin's predator-prey model, but with a reversal of the roles for predator and prey; this is another way to conceptualize the symbiosis between the two classes within a capitalist economy. The aforementioned argument is also examined in relation to the double movement of Karl Polanyi and the inverse U-shaped curve proposed by Simon Kuznets.
Economics
Keywords: Kaleckian; Sraffian; aggregate factor income distribution; aggregate human capital; aggregate labor productivity; business fluctuations; capacity; capital; cycles; employment; general aggregative models: Marxian; intangible capital; intergenerational income distribution; investment; one; two; and multisector growth models; unemployment; wages

Local Embeddedness - Pickles, John (International Encyclopedia of Geography: People, the Earth, Environment and Technology, 2016)
In economic geography and economic sociology, embeddedness refers to the ways in which relational, institutional, and cultural contexts shape economic life. In contrast to the undersocialized and utilitarian assumptions of neoclassical economics, rational choice theory, and new institutional economics, theories of embeddedness focus on the ways in which markets and society are variously articulated in particular societies, organizations, and places. Embeddedness in this sense is associated first and foremost with the work of Karl Polanyi. Polanyi argued that the market generally sought to disembed itself from social regulation, while society responded by attempting to socialize and regulate (re-embed) the excesses of unregulated markets. It is also associated with the work of Granovetter in economic sociology, who cautioned against oversocializing, as well as undersocializing, the economy, in favor of a much more detailed analysis of the specific ways in which social relations structured economic practices.
Geography; Sociology
Keywords: POLANYI; Karl; 1886-1964; culture; economy; embeddedness; institutions; society; undersocialized

Critical reflections on social enterprise through a polanyian lens - Roy, M., S., Grant (Social Enterprise Research Colloquium Australasia, 2016)
N/A
Keywords: social enterprise

Polanyi In Our Times - Saval, Nikal (The Nation, 2016)
N/A
Keywords: Greek crisis; biography; blog

"Let Them Eat Stuffed Peppers": An Argument of Images on the Role of Food in Understanding Neoliberal Austerity in Greece - Sutton, David (Gastronomica, 2016)
This paper focuses on how discourses of food have shaped understandings of what is at stake in the Greek crisis. Drawing from Karl Polanyi's concept of "embeddedness," I argue that food is central to Greek interpretations of neoliberal policies and processes because of its centrality to Greek culture and identity. Food has also been a site of contested practices of "solidarity" and "charity" by which new social experiments are emerging in the wake of the breakdown of the welfare state. In arguing for food's centrality in the reshaping of Greek sociability, I will suggest that food be thought of not simply as a "topic" for anthropological investigation, but as a master-concept on the level of "kinship," "ritual," or "exchange" in any anthropological analysis of contemporary life.
Anthropology; Food Studies
Keywords: Greece; Greek crisis; Kalymnos; Oriental and African Studies; austerity (economics); critical food studies; food metaphors; food studies; kinship; neoliberalism; solidarity

Proprietary Law Schools and the Marketization of Access to Justice - Tejani, Riaz (Social Science Research Network, 2016)
The rise of for-profit law schools in the United States highlights the interplay of political and moral economy in the reproduction of legal expertise. This article offers ethnographic evidence from one ABA-accredited for-profit law school pseudonymously labeled New Delta School of Law. The article posits New Delta as a case study in market fundamentalism of the kind first theorized by Hungarian economist Karl Polanyi. Polanyi defined global capital as a “double movement” between free marketeerism on the one hand and countervailing social protectionism on the other. Treating this as incomplete, social philosopher Nancy Fraser has since argued that the emancipatory new social movements form a third element in what should more properly be considered a “triple movement.” In this article, I argue that for-profit law schools such as New Delta support Fraser’s revision. Drawing in capital commitments from large institutional investors with promises of high returns on the basis of guaranteed federal student loan dollars, New Delta recruits disproportionately from minority and low-income communities while offering low chances of bar passage and legal employment. By marrying free marketeerism with the discourse of emancipation, the school has successfully evaded scrutiny.
Law; Legal Studies
Keywords: anthropology; economic; finance; law; legal education; markets; morals; neoliberalism; race; regulation; triple movement

Local Trade and Exchange/Employment Systems (LETS) in Future Eco-sustainable Societies - Westra, Richard (Anthropology in Action, 2016)
All communities of practice must face questions relating to the material economic foundations of future sustainable societies. David Graeber, Karl Polanyi and Karl Marx each have produced typologies of possible types of economy, synthesised as: (1) the principle of individual reciprocity, (2) the market principle of capitalism, and (3) the planning principle of the state. I apply this synthesis to recent proposals for community change advanced by Bill McKibben and David Korten concerning economic scale and the re-localising of production and consumption sundered by globalisation, focused on the local exchange and trading system (LETS). The operationalising of LETS draws upon Adam Smith's view of markets as face-to-face exchanges of goods taking place in small morality-bound communities. Smith, McKibben and Korten conflate two different meanings of the term 'exchange'. To understand the role LETS may play in future sustainable economies in communities of practice demands treatment of this problem.
Anthropology
Keywords: MCKIBBEN; Bill; 1960-; capitalism; communities of practice; community; eco-sustainability; economy; globalization; local exchange and trading systems; markets; sustainability; sustainable societies

Singapore’s Social Contract Trilemma - Yeoh, Lam Keong; Auyong, Hawyee; Yeo, Andrew Zhi Jian (Globalization and Democracy in Southeast Asia, 2016)
The last 50 years of nation building has firmly established Singapore as a globally competitive and highly successful economy and city-state with one of the highest per capita incomes in the world. Singapore has achieved a prosperity undreamed of by its founders. How successfully Singapore can evolve into a fully developed nation, with a firm sense of national belonging, social cohesion, political legitimacy and participation—and not just a strong and successful developmental state—will depend on the extent to which the country is able to translate this success to broader social protection and democratic participation for her people, and the extent to which the country is able to forge a common national identity.
Political Science
Keywords: FRASER; Nancy; Singapore; democracy; double movement; globalization; neo-Polanyian; policy studies; triple movement

The Methodology of Polanyi's Great Transformation - Zaman, Asad (Economic Thought, 2016)
Polanyi's book, The Great Transformation, provides an analysis of the emergence and significance of capitalist economic structures which differs radically from those currently universally taught in economic textbooks. This analysis is based on a methodological approach which is also radically different from existing methodologies for economics, and more generally social science. This methodology is used by Polanyi without explicit articulation. Our goal in this article is to articulate the methodology used in this book to bring out the several dimensions on which it differs from current approaches to social science. Among the key differences Polanyi provides substantial scope for human agency and capability to change the course of history. He also shows that the social, political and economic spheres of human existence are deeply interlinked and cannot be analysed in isolation, as current approaches assume. KM - see Mayhew's (2016) commentary on this paper.
Economics
Keywords: capitalism; liberalism; methodology; social science

Economics as Social Science: Economics imperialism and the challenge of interdisciplinarity - Marchionatti, Roberto; Cedrini, Mario (Taylor & Francis, 2016)
There is a growing consensus in social sciences that there is a need for interdisciplinary research on the complexity of human behavior. At an age of crisis for both the economy and economic theory, economics is called upon to fruitfully cooperate with contiguous social disciplines. The term ‘economics imperialism’ refers to the expansion of economics to territories that lie outside the traditional domain of the discipline. Its critics argue that in starting with the assumption of maximizing behaviour, economics excludes the nuances of rival disciplines and has problems in interpreting real-world phenomena. This book focuses on a territory that persists to be largely intractable using the postulates of economics: that of primitive societies. In retracing the origins of economics imperialism back to the birth of the discipline, this volume argues that it offers a reductionist interpretation that is poor in interpretative power. By engaging with the neglected traditions of sociological and anthropological studies, the analysis offers suggestions for a more democratic cooperation between the social sciences. Economics as Social Science is of great interest to those who study history of economic thought, political economy and the history of economic anthropology, as well as history of social sciences and economic methodology.
Keywords: economic theory; economics imperialism

Cucumbers and Courgettes: Rural Workfare and the New Double Movement in Hungary - Hann, Chris (Intersections. East European Journal of Society and Politics, 2016)
The paper is an application of the economic anthropology of Karl Polanyi to contemporary rural Hungary. After addressing the influence of Polanyi’s critique of market society and his standing in the discipline of anthropology, the main focus is the community of Tázlár on the Danube-Tisza interfluve. The paper traces the history of the ‘fictitious commodities’ of land and labour in this relatively isolated settlement, which was not fully integrated into the national society until the socialist era. The innovative symbiosis of household and cooperative farming was destroyed in the 1990s. In the depressed economic climate of today, workfare schemes are popular because they treat villagers as human beings rather than as commodities to be exploited for maximum profit. The workfare initiatives of populist power holders can be interpreted as one facet of a complex ‘double movement’ in which postsocialist society seeks to defend itself against the domination of the market.
Publisher: MTA Társadalomtudományi Kutatóközpont Kisebbsegkutató Intézet
Keywords: (post)socialism; Danube-Tisza interfluve; Hungary; Karl Polanyi; double movement; fictitious commodities; neoliberalism; workfare

Embeddedness, Redistribution and Double Dependence: Polányi-reception Reconsidered - Lengyel, György (Intersections. East European Journal of Society and Politics, 2016)
This article – a modified version of a lecture – is a contribution to the reception of Polányi in the West and the East, more precisely, to the inquiry about what impact Polányi’s views have had on American and Hungarian economic sociology, which are the contact points between the two, and what research perspectives they offer. It concentrates on the perception of embeddedness and redistribution, not touching on other views unless they are conducive to the comprehension of certain connections. Polányi’s oeuvre is so rich and it has inspired such a wide range of debates that a conclusive review is impossible within a single article. It is hoped however that the polemic on the concept of embeddedness may be illuminating and also the aftermath of the forms of integration, particularly redistribution, important. The concept of double dependence is touched upon as well, for it grasps an essential feature of the post-socialist Eastern European economies. It is worth mentioning it in this context, for Polányi’s influence left its mark upon it and it is also related to the conceptual apparatus of the substantive view.
Publisher: MTA Társadalomtudományi Kutatóközpont Kisebbsegkutató Intézet
Keywords: Polányi; dependent market economy; double dependenc; embeddedness; fictitious commodities; forms of integration; post-socialist transformation; redistribution; state socialism; varieties of capitalism

Sustaining Democracy in an Era of Free Markets: Karl Polanyi’s Perspectives on the Politics of Finance - Scheiring, Gábor (Intersections. East European Journal of Society and Politics, 2016)
With the contemporary crisis of liberal democracy and the rise of illiberalism in the aftermath of the global financial crisis we need a theoretical framework that links modernization, crises and the fate of democracy. In my paper I attempt to show that Polanyi’s thinking represents such a framework. I focus on Polanyi’s historically informed political economic analysis of the tensions between liberal finance and liberal democracy. In the first section I reconstruct Polanyi’s political stance regarding democracy, socialism and the market. Based on this I will bring to the fore his often neglected views regarding the commodification of money and the tensions between international finance and democracy. Polanyi shows that monetary policy is not a technical but a deeply political question with major social implications. In the final section of my paper I conclude that Polanyi’s theory of the double movement and fictitious commodification can only be understood once we strip it of its excessive functionalism and bring it into dialogue with his political views. Polanyi urges to preserve the market by protecting the economy and society from the damages of excessive commodification: markets need to be protected from themselves.
Sociology; Economics
Keywords: Polanyi; democracy; double movement; fictitious commodities; finance

Risk Markets and the Landscape of Social Change - Breger Bush, Sasha (International Journal of Political Economy, 2016)
With the critical derivatives and financialization literatures as background, I argue in this essay that risk markets (i.e., derivatives and insurance markets) play an integral role in insulating global neoliberalism from popular and elite demands for reform, as well as from the related imposition of new forms of government intervention. Inspired by Polanyi’s “double movement” and Bryan and Rafferty’s (2006) notion of “blending” in derivatives markets, the argument rests upon the insight that risk markets transform social risk into individual cost, resulting in potentially large but subtle implications for global prospects for social change. After providing a taxonomy of risk instruments that emphasizes their growing role in managing important social risks, I describe and provide brief case studies of two pathways through which risk markets help to protect the neoliberal order from political threats. The first involves the political positioning of insurance and derivatives instruments and markets as “solutions” to global social problems. The second involves the manner in which insurance and derivatives products generate “political moral hazards” that discourage support for new kinds of global policies and structures. As such, this essay contributes to the growing body of critical political economy literature on financialization, financial innovation, and derivatives and insurance markets.
Political Science
Keywords: Polanyi; derivative securities; derivatives; finance; financialization; innovation; insurance; insurance exchanges; neoliberalism; social change